Understanding Respiratory Restrictions as a Function of the Scoliotic Spinal Curve in Thoracic Insufficiency Syndrome: A 4D Dynamic MR Imaging Study. Issue 4 (1st April 2020) - Udupa, Jayaram K.; Tong, Yubing; Capraro, Anthony; McDonough, Joseph M.; Mayer, Oscar H.; Ho, Suzanne; Wileyto, Paul; Torigian, Drew A.; Campbell, Robert M.
Abstract : Background: Over the past 100 years, many procedures have been developed for correcting restrictive thoracic deformities which cause thoracic insufficiency syndrome. However, none of them have been assessed by a robust metric incorporating thoracic dynamics. In this paper, we investigate the relationship between radiographic spinal curve and lung volumes derived from thoracic dynamic magnetic resonance imaging (dMRI). Our central hypothesis is that different anteroposterior major spinal curve types induce different restrictions on the left and right lungs and their dynamics. Methods: Retrospectively, we included 25 consecutive patients with thoracic insufficiency syndrome (14 neuromuscular, 7 congenital, 4 other) who underwent vertical expandable prosthetic titanium rib surgery and received preimplantation and postimplantation thoracic dMRI for clinical care. We measured thoracic and lumbar major curves by the Cobb measurement method from anteroposterior radiographs and classified the curves as per Scoliosis Research Society (SRS)-defined curve types. From 4D dMRI images, we derived static volumes and tidal volumes of left and right lung, along with left and right chest wall and left and right diaphragm tidal volumes (excursions), and analyzed their association with curve type and major curve angles. Results: Thoracic and lumbar major curve angles ranged from 0 to 136 and 0 to 116 degrees, respectively. A dramatic postoperative increase in chest wall and diaphragmatic excursion was seen qualitatively. All components of volume increased postoperatively by up to 533%, with a mean of 70%. As the major curve, main thoracic curve (MTC) was associated with higher tidal volumes (effect size range: 0.7 to 1.0) than thoracolumbar curve (TLC) in preoperative and postoperative situation. Neither MTC nor TLC showed any meaningful correlation between volumes and major curve angles preoperatively or postoperatively. Moderate correlations (0.65) were observed for specific conditions like volumes at end-inspiration or end-expiration. Conclusions: The relationships between component tidal volumes and the spinal curve type are complex and are beyond intuitive reasoning and guessing. TLC has a much greater influence on restricting chest wall and diaphragm tidal volumes than MTC. Major curve angles are not indicative of passive resting volumes or tidal volumes. Level of Evidence: Level II—diagnostic.